THE EFFECT OF GIVING DETERGENTS TO THE GROWTH OF Azolla microphylla IN BRACKISH WATER - Parbo, Annisa Presti; Effendi, Irwan; Nedi, Syahril (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2019)
This research conducted on March to April 2019 with the aim of knowing the effect of detergent on the growth of A. microphylla. The results showed wet weight growth ranging from 2-23.81 grams (control) and 1.43-8.35 grams (addition of detergent). Absolute weight growth ranges from 3.63-8.47 grams and 1.77-3.28 grams. Growth in the number of colonies between 39.66-295 colonies and 37.66-98.33 colonies. Growth doubling time day 3-23 and 3.63-7.66 days. The growth of wet weight and the number of colonies of A. microphyla increased in each data collection on the control treatment media, while the addition of detergent treatment increased on the day 5 and day 10 and on the day 15 and day 20 decreased.